PHYTOCHEMICAL COMPOUNDS OF SEA CUCUMBER CONSUMED AFTER EXERCISE PROVEN TO SIGNIFICANTLY LOWER NF-KB LEVELS - Yulfadinata, A.; Handayani, S. G.; Ayubi, N. (Rehabilitation and Recreation, 2025)
Purpose. The aim of this study was to analyze the effects of post-exercise sea cucumber supplementation on NF-kB levels as a biomarker of inflammation. Material. An experimental study with a pre-test and post-test group design was conducted by comparing the placebo group (K1) with the treatment group (K2) which was given a 500 mg dose of sea cucumber supplement. A total of eighteen healthy men participated in this study. The method of examining NF-kB levels uses ELISA (Enzyme-linked immunosorbent assay). Results. The characteristics of the research subjects were age, height, weight, BMI, and blood pressure (systolic and diastolic). The results of the t-test of the characteristics of the research subjects showed that there was no significant difference between K1 and K2 (p≥0.05). Furthermore, the results of the study reported that group K1 given placebo after exercise could not significantly reduce NF-kB levels (p>0.05). Group K2 given sea cucumber supplementation after exercise could significantly reduce NF-kB levels (*p<0.05). The phenolic and polyphenol content in sea cucumber supplementation has anti-inflammatory properties that positively impact reducing NF-kB levels after exercise. In addition, peptides in sea cucumbers function as reducing agents that can protect cells from increased NF-κB signaling, phosphoinositide 3-kinase or Akt signaling pathways, and mitogen-activated protein kinase. Decreased NF-kB levels have the potential to reduce proinflammatory cytokines such as TNF-a which are triggers of delayed onset muscle soreness after exercise. Conclusions. It can be concluded that sea cucumber supplementation with a dose of 500 mg given after 24 hours of physical session can reduce NF-kB levels. In people who exercise regularly, sea cucumber supplementation is highly recommended as an additional supplement to suppress inflammation after exercise.